2007
DOI: 10.1016/j.ejca.2007.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Cell lines from MYCN transgenic murine tumours reflect the molecular and biological characteristics of human neuroblastoma

Abstract: Overexpression of the human MYCN oncogene driven by a tyrosine hydroxylase promoter causes tumours in transgenic mice that recapitulate the childhood cancer neuroblastoma. To establish an in vitro model to study this process, a series of isogenic cell lines were developed from these MYCN-driven murine tumours. Lines were established from tumours arising in homozygous and hemizygous MYCN transgenic mice. Hemizygous tumours gave rise to cell lines growing only in suspension. Homozygous tumours gave rise to simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 17 publications
2
38
0
Order By: Relevance
“…NHO2A cells have been derived from the transgenic TH-MYCN neuroblastoma mouse model that develops aggressive neuroblastoma and shows many features of the human childhood disease [30]. NHO2A cells were engrafted subcutaneously into immune-competent mice and tumours allowed to reach 200 mm 3 before treatment commenced.…”
Section: Resultsmentioning
confidence: 99%
“…NHO2A cells have been derived from the transgenic TH-MYCN neuroblastoma mouse model that develops aggressive neuroblastoma and shows many features of the human childhood disease [30]. NHO2A cells were engrafted subcutaneously into immune-competent mice and tumours allowed to reach 200 mm 3 before treatment commenced.…”
Section: Resultsmentioning
confidence: 99%
“…Western blotting was performed according to previously published methods,13 using the MYCN100 antibody at 1:50, a monoclonal actin (Dako) antibody at 1 in 500, and a goat anti-mouse secondary antibody for both. A selection of cell line lysates were also included as positive and negative controls: MYCN -amplified IMR-32,13 MYCN non-amplified SHSY5Y,13 LAN-614 and a cell line established from a transgenic mouse tumour homozygous for the MYCN transgene (3402A) 15…”
Section: Methodsmentioning
confidence: 99%
“…In stark contrast, MycN overexpression in neuroblastoma tumor cell lines (NHO2A cells) derived from TH-MYCN þ / þ mouse tumors, 23 or primary ganglia cells from 6-week-old WT mice, caused marked cell death in the absence of trophic factor (Figure 1g). These results suggested that the barriers present in normal adult cells exposed to oncoprotein stress were transiently and specifically repressed in perinatal neuroblasts.…”
Section: Mycn Protects Neuroblastoma Precursor Cells From Death Stimulimentioning
confidence: 97%
“…22 Importantly, this model fully recapitulates the p53 wildtype (WT) status, chemosensitivity and p53-dependent apoptotic responses of human neuroblastoma. 23,24 We first used neuroblastoma precursor cells (that is, perinatal primary sympathetic ganglia from the TH-MYCN þ / þ mice) to investigate the effects of MycN expression on the response to death stimuli and the replicative potential of these precancer cells.…”
Section: Mycn Protects Neuroblastoma Precursor Cells From Death Stimulimentioning
confidence: 99%